KOŚCIOŁY POKOJU W JAWORZE I ŚWIDNICY – PRACE KONSERWATORSKIE WNĘTRZA I WYPOSAŻENIA, JAKO PRZYKŁAD OCHRONY BUDOWLI WPISANYCH NA LISTĘ ŚWIATOWEGO DZIEDZICTWA - Małgorzata Korpała (Ochrona Dziedzictwa Kulturowego, 2017)
Churches of Peace in Jawor and Świdnica, inscribed in the World Heritage List, are unique examples of religious monuments which were created despite many unfavourable circumstances, and survived till today while preserving their original function, decorations and furnishings. The article discusses crucial principles of conservation work in both buildings, which has been carried out since the beginning of the 1990s. Positive results of conservation work, preserving the authenticity of substance, were possible mainly due to inscribing the building in the UNESCO World Cultural Heritage List. Preserving the authenticity of those monuments was the priority during the realised conservation work on the interior decoration and furnishings. That is why the Churches of Peace in Jawor and Świdnica maintained their authentic original décor from the turn of the 17th and 18th century.